2018
DOI: 10.1371/journal.pone.0207798
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relationship between serum vitamin D level and measles antibody titer: A cross-sectional analysis of NHANES, 2001-2004

Abstract: BackgroundIn recent years, researchers have illuminated many non-skeletal actions of vitamin D including host defense against various pathogens and vaccine immunology. The purpose of our study was to explore the potential association between serum vitamin D levels and measles antibody titers.MethodsThe biochemical profiles and de-identified information were accessed from the 2001 to 2004 National Health and Nutrition Examination Survey (NHANES). Participants were divided into quartiles according to their measl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A cross-sectional study found that low serum vitamin D levels were associated with higher antibody titers against partial influenza virus vaccines in children ( 26 ). Another cross-sectional analysis of the National Health and Nutrition Examination Survey (NHANES) highlighted a negative association between serum 25(OH)D levels and measles antibody titers ( 27 ). Many studies have demonstrated the expression of the vitamin D receptor (VDR) in almost all immune cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study found that low serum vitamin D levels were associated with higher antibody titers against partial influenza virus vaccines in children ( 26 ). Another cross-sectional analysis of the National Health and Nutrition Examination Survey (NHANES) highlighted a negative association between serum 25(OH)D levels and measles antibody titers ( 27 ). Many studies have demonstrated the expression of the vitamin D receptor (VDR) in almost all immune cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over time, the median antibody titers increased in the deficient vitamin D group, while a restrained increase was observed in subjects with higher 25(OH)D levels. In this context, several studies have reported an inverse relationship between serum 25(OH)D and virus antibody titers [ 29 , 30 , 31 ]. Mechanistically, vitamin D has been shown to hamper the production of immunoglobulins [ 32 , 33 , 34 , 35 ], attenuating the humoral immune reaction induced by viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation also agrees with pneumococcal vaccination, in which the authors observed no correlation between VitD level and the magnitude of anti- Streptococcal pneumoniae antibody levels 49 . Alternatively, studies on human papillomavirus (HPV), rubella, and measles vaccinations have demonstrated that VitD levels were inversely proportional to lower antibody titers 50 52 . However, these findings were inconsistent with the observations that lower VitD levels were associated with a poorer prognosis in COVID-19 and other respiratory tract infections 17 , 21 , 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%